Integrating Digital Tools to Enhance Creativity and Aesthetic Skills in Fine Arts Education - Raxmonova E’zoza Zoir qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article examines the integration of digital tools in fine arts education to enhance students’ creativity, aesthetic perception, and visual literacy. It explores project-based learning, interactive digital platforms, and student-centered approaches as strategies to foster engagement, critical thinking, and innovative artistic expression. The study highlights the importance of creating a supportive and flexible learning environment that encourages experimentation, reflective practice, and cultural awareness.